Permainan Sains Problem-Solving Cardboard Box Lego dan Kreativitas Anak Usia Dini - Fauziah, Sarah; Mulyana, Edi Hendri; Mulyadi, Sima (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2021)
Media, in general, is a means of providing information to the recipient of the message, namely the child. The game is a medium that is used as a medium of play for children that can be used as a means of learning. This game uses a problem-solving learning method, namely problem-solving. It is hoped that this method can find solutions in fostering children’s creativity. Therefore, this research is to improve children’s cognitive abilities in solving a problem (problem-solving). Thus, this research develops problem-solving game media to facilitate children’s creativity by using cardboard box lego game media. In designing this game media, it refers to the 2013 curriculum. The 2013 curriculum is expected to facilitate aspects of children’s cognitive development for their creativity. This study aims to describe the basic needs of game media and develop a cardboard box lego problem-solving science game to facilitate early childhood creativity. The method used in this research is the Educational Design Research (EDR) floating method. Learning science in early childhood is still considered quite tricky, but this will be easy to overcome with the right and appropriate and adequate media and teaching materials. Based on the literature study that has been done, many science game media are not by the child’s development stage, which should adjust to aspects of child development that refer to the 2013 curriculum. So based on the needs and findings in the field, researchers will develop a cardboard box kego problem-solving science game to facilitate early childhood creativity.